Sears and Zemansky's University physics: with modern physics, 11th edition - Young Hugh D., Freedman Roger A. (Dorling kindsley, Delhi, 2009)
Physics
UGC XIth Five Year Plan 2009-2010
ENGLISH
Keywords: Sears and Zemansky's University physics: with modern physics, 11th edition; Physics; Physics